Social Networks and Peer Effects at Work - Julie Beugnot; Bernard Fortin; Guy Lacroix; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2013)
This paper extends the standard work effort model by allowing workers to interact through networks. We investigate experimentally whether peer performances and peer contextual effects influence individual performances. Two types of network are considered. Participants in Recursive networks are paired with participants who played previously in isolation. In Simultaneous networks, participants interact in real-time along an undirected line. Mean peer effects are identified in both cases. Individual performances increase with peer performances in the recursive network. In the simultaneous network, endogenous peer effects vary according to gender: they are large for men but not statistically different from zero for women.
Keywords: C91; J16; J24; J31; M52; 330; peer effects; social networks; work effort; piece rate; experiment